Interface entre neuropsicologia e psicopatologia: funções executivas, variáveis clínicas, qualidade de vida e funcionalidade na depressão e no transtorno bipolar - Cotrena, Charles (Pontifícia Universidade Católica do Rio Grande do Sul, 2015)
Made available in DSpace on 2015-08-27T02:21:37Z (GMT). No. of bitstreams: 1 000472635-Texto+Parcial-0.pdf: 567 bytes, checksum: e98dd54c3b65934b530ebbe3119c8cc9 (MD5) Previous issue date: 2015 === Several neuropsychological and psychopathological studies have sought to identify the cognitive features associated with different psychiatric conditions and their relationship with clinical and demographic variables, functioning and quality of life. Major depressive (MDD) and bipolar disorder (BD) have been the subject of several such investigations, although findings are still preliminary and limited in their clinical applicability and generalizability due to the methodological heterogeneity of studies in the area. Therefore, the goal of this research was to investigate the relationship between cognitive, clinical and demographic features as well as quality of life and functioning in a naturalistic sample of patients with MDD and TB as compared to healthy subjects. The first study investigated differences between the cognitive performance of patients with MDD, BDI, BDII and adults with no mood disorders. Patients with MDD showed impairments in sustained and divided attention, working memory, verbal fluency, inhibitory control and decision making, especially in timed tasks. Patients with BDII showed variable performance and high rates of impairment in attentional interference control. Finally, patients with BDI showed consistently poorer performance than the remaining groups on most cognitive tasks, as well as greater impairments in attention and inhibition than individuals with MDD. In light of these findings and studies regarding the variability of cognitive profiles within diagnostic categories, the second study aimed to identify executive functioning profiles in mood disorders using hierarchical cluster analysis. Four distinct groups of participants were identified. The first was characterized by the absence of executive impairment and was mostly composed of control participants, while the second group showed slight impairments in inhibitory control, divided attention, working memory and verbal fluency. Clusters 3 and 4, composed clinical participants only, showed impairments in inhibitory control and working memory (cluster 3), and inhibitory control and cognitive flexibility (cluster 4). Given the heterogeneity of profiles identified, and the known impact of cognition on functional outcome and quality of life in mood disorders, the third study sought to identify profiles of functioning and quality of life in MDD and BD, as well as their association with clinical, demographic and cognitive variables. The subscales of the WHODAS 2. 0 and WHOQOL-BREF questionnaires were submitted to a hierarchical cluster analysis, which assigned patients into three groups. The first, composed mostly of control participants and a small percentage of psychiatric patients, had the highest scores on these measures. The second group obtained intermediate scores, and contained mostly individuals with MDD and BDII, and, to a lesser extent, BDI and control participants. Lastly, cluster 3 had the worst overall performance and was composed predominantly of patients with TBI, and some patients with TBII and TDM. No control participants were included in this group. Poor functioning and quality of life were associated with impairments in inhibitory control, decision making and attentional control. Together, these studies provided important data regarding cognition, functioning and quality of life in mood disorders, revealing a continuum of severity and several possible targets for therapeutic approaches developed specifically for these diagnostic categories. === Atualmente a neuropsicologia contribui à psicopatologia pela busca e identificação de características cognitivas de diferentes quadros psicopatológicos, e sua relação com fatores clínicos, demográficos, de capacidade funcional e qualidade de vida. Neste contexto, o transtorno depressivo maior (TDM) e o transtorno bipolar (TB) tem sido alvo de diversas investigações, embora ainda preliminares e com limitada aplicabilidade clínica e generalizabilidade devido a sua heterogeneidade metodológica. Assim, o objetivo desta pesquisa foi investigar a interrelação entre fatores cognitivos, clínicos, demográficos, a qualidade de vida e funcionalidade de amostra naturalística de pacientes com TDM e TB, comparados a participantes saudáveis. O primeiro estudo visou a identificar diferenças entre o TDM, TBI, TBII e participantes controles quanto aos processos neurocognitivos de funções executivas, atencão e velocidade de processamento. Pacientes com TDM apresentaram prejuízos na atenção sustentada e dividida, memória de trabalho, fluência verbal livre, controle inibitório e tomada de decisão, especialmente em tarefas envolvendo avaliações temporais de desempenho. Pacientes com TBII apresentaram desempenho heterogêneo, e alta prevalência de déficits no controle de interferências atencionais. Por último, pacientes com TBI apresentaram maior número de componentes executivos prejudicados quando comparados ao restante dos grupos, além de maior prejuízo atencional e inibitório do que o TDM .Com base nestes achados e evidências quanto à variabilidade de perfis cognitivos dentro de diferentes categorias diagnósticas, o segundo estudo buscou identificar perfis de funcionamento executivo nos transtornos do humor por meio de análise de clusters. Foram solicitados quatro agrupamentos distintos de participantes. O primeiro caracterizou-se pela ausência de prejuízos executivos e predominância de participantes controles, e o segundo por prejuízos leves no controle inibitório, atenção dividida, memória de trabalho e fluência verbal. Os clusters 3 e 4, compostos unicamente por participantes clínicos, apresentaram prejuízos inibitórios e mnemônicos de trabalho (cluster 3) e comprometimento no controle inibitório e flexibilidade cognitiva (cluster 4). Em vista da heterogeneidade de perfis identificados, e do conhecido impacto da cognição no desfecho funcional e na qualidade de vida de pacientes com transtornos do humor, o terceiro estudo buscou especificar perfis de funcionalidade e qualidade de vida no TDM e TB, e sua associação com variáveis clínicas, demográficas e cognitivas.A análise de clusters hierárquicos baseada nas subescalas dos questionários WHODAS 2. 0 e WHOQOL-BREF identificaram três perfis de qualidade de vida e de funcionalidade. No perfil 1, enquadraram-se a maioria dos participantes controle, assim como alguns membros dos grupos clínicos, apresentando os maiores escores de funcionalidade e qualidade de vida da amostra. O cluster 2, em posição intermediária, foi composto em maior parte por pacientes portadores de TDM e TBII e em menor proporção por pacientes com TBI e controles. Por último, o cluster 3 apresentou o pior desempenho geral e foi composto predominantemente por pacientes portadores de TBI, alguns pacientes com TBII e com TDM, e ausência de controles. Prejuízos na funcionalidade e qualidade de vida associaram-se a alterações no controle inibitório, tomada de decisão e controle atencional. Em conjunto, os estudos ofereceram dados importantes a respeito dos perfis cognitivos, de funcionalidade e qualidade de vida nos transtornos do humor, permitindo a identificação de um continuum de gravidade e apontando possíveis focos para abordagens terapêuticas desenvolvidas para estas categorias diagnósticas.